Dashboards for improving patient care: Review of the literature. Issue 2 (February 2015) - Dowding, Dawn; Randell, Rebecca; Gardner, Peter; Fitzpatrick, Geraldine; Dykes, Patricia; Favela, Jesus; Hamer, Susan; Whitewood-Moores, Zac; Hardiker, Nicholas; Borycki, Elizabeth; Currie, Leanne
Highlights There is heterogeneity in the setting where dashboards are used. There is heterogeneity in the design of dashboards and users targeted. Dashboard use may be associated with improved outcomes in some contexts. It is unclear what dashboard characteristics are related to improved outcomes.